Examining the relationship between HbA1c and diabetes risk models in a European population indicates a lower threshold to identify 'high risk' is required. (May 2016) - Gray, Benjamin J; Bracken, Richard M; Turner, Daniel; Morgan, Kerry; Thomas, Michael; Williams, Sally P; Williams, Meurig; Rice, Sam; Stephens, Jeffrey W; ,
This study examined whether changes in HbA1c values are reflected in the risk scores and categories of four validated risk-assessment tools (QDiabetes, Leicester Risk Assessment, Finnish Diabetes Risk Score and Cambridge Risk Score). Retrospective analysis was performed on 651 individuals with no prior diagnosis of cardiovascular disease or diabetes who participated in a UK workplace-based risk-assessment initiative. There were significant positive correlations ( p  < 0.01) revealed between HbA1c values and predicted risk scores: QDiabetes ( r  = 0.362), Leicester Risk Assessment ( r  = 0.315), Finnish Diabetes Risk Score ( r  = 0.202) and Cambridge Risk Score ( r  = 0.335). HbA1c values increased within risk prediction categories, and at 'high-risk' categories, median HbA1c values were at least 39 mmol mol −1 (5.7%) irrespective of gender or risk-assessment model. Overall, an association is present between increases in HbA1c scores and predicted risk of type 2 diabetes. Furthermore, the 'high-risk' median HbA1c values in each of the risk assessments are more akin to the lower American recommendations rather than those suggested by the UK expert group.